Exploring the Influence of Demographic Factors on Occupational Stress in Inpatient Nursing - Pornomo, Jeki; Mujtahidah, Mujtahidah (Science Tech Group, 2026)
Occupational stress among nurses is a persistent and multidimensional challenge in healthcare systems worldwide. As frontline caregivers in inpatient settings, nurses face physical and emotional demands that vary considerably according to individual demographic characteristics. Understanding how these characteristics shape stress experiences is essential for designing targeted and effective institutional interventions. This study aimed to explore and describe the influence of demographic factors specifically age, gender, work experience, marital status, and educational background on occupational stress levels among inpatient nurses in an Indonesian hospital. A descriptive quantitative design was employed, supplemented by semi-structured interviews. Data were collected from 63 nurses using a structured questionnaire adapted from the Nursing Stress Scale and analysed through descriptive and inferential statistics. Interview data were analysed thematically. The majority of respondents experienced mild stress (57.1%), followed by moderate stress (36.5%) and high stress (6.4%). Nurses aged 31–40 exhibited the highest rates of moderate to high stress (57.1%), while younger nurses (20–30) predominantly experienced mild stress (63.4%). Female nurses showed higher rates of high stress (7%) compared to male nurses (0%). Nurses with 5–10 years of experience and those holding a Bachelor's degree reported greater moderate-to-high stress than their counterparts. Married nurses consistently reported higher stress levels than unmarried nurses. The dominant stressors across all demographic groups were workload, conflict with physicians, and uncertainty in patient treatment. Demographic factors significantly differentiate occupational stress profiles among inpatient nurses. Institutional support including stress management training, workload adjustments, and improved interprofessional communication is critical to alleviating stress and sustaining both nurse well-being and patient care quality.